Percutaneous treatment of liver hydatid cysts in 190 patients: a retrospective study. (June 2017) - Kahriman, Guven; Ozcan, Nevzat; Dogan, Serap; Karaborklu, Oguz
Background: Hydatid liver disease (HLD) is a significant health problem, especially in endemic areas worldwide. Percutaneous treatment is an effective alternative therapeutic option. Purpose: To present the clinical and radiological results of percutaneous treatment of HLD in 190 patients. Material and Methods: Percutaneous treatment of HLD between April 2005 and March 2015 was analyzed retrospectively. The demographic data, numbers and types of cysts, initial and final volumes of the cysts, types of percutaneous treatment, and procedure-related complications were determined. Results: A total of 190 patients (95 male patients and 95 female patients; age range, 5–82 years) with 283 liver hydatid cysts who underwent percutaneous treatment were included in the study. Of the 283 cysts, 234 (83%) were cystic echinococcosis CE1, 31 (11%) were CE3a, and 18 (6%) were CE2 cysts, according to the World Health Organization (WHO) classification. The percutaneous procedure was successful in all patients. A total of 12 (6.3%) major complications, including anaphylaxis, allergic skin reaction, perihepatic hemorrhage, and cavity infection, were seen. No mortality was noted. Recurrence in one patient and an additional cyst in one patient were seen. All patients were asymptomatic during the follow-up period. Mean volume reduction was 77.5%, with a mean follow-up period of 18 months. Conclusion: Percutaneous treatment is an effective and safe method for the treatment of HLD. It should be regarded as a first-line treatment method for uncomplicated hydatid cysts.